MUTU BAKSO IKAN EKOR KUNING (Caesio cuning) DENGAN PENAMBAHAN REBUNG (Dendrocalamus asper) - Christian Sinaga; Netti Herawati; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to get the exact formulation of the slurry shoots with yellowtail fish meat in the manufacture of composite flour meatballs using sago starch and tapioca starch as a filler. The expected benefits of this research is the improve of the nutritional value of the meatballs with the addition of bamboo shoots and increase the diversity of fishery product processing and dissemination of fish balls. The method used in this research is completely randomized design (CRD) with 5 treatments and 3 replications. The treatment in this study is P1 (25% bamboo shoots : 35% yellowtail fish), P2 (20% bamboo shoots : 40% yellowtail fish), P3 (15% bamboo shoots : 45% yellowtail fish), P4 (10% bamboo shoots : 50% yellowtail fish), P5 (5% bamboo shoots : 55% yellowtail fish). The results of this study showed that the addition ratio of shoots on yellowtail fish balls significant effect on water content, fiber content and protein levels as well as color, aroma, flavor and texture of the meatballs are descriptive, but no effect was not apparent to the hedonic test on the attributes of color, texture and an overall assessment. The best treatment is P1 (25% bamboo shoots : 35% yellowtail fish). Keywords: MeatBall, yellowtail fish, bamboo shoots.